2017
DOI: 10.1007/s00586-017-5170-z
|View full text |Cite
|
Sign up to set email alerts
|

Do position and size matter? An analysis of cage and placement variables for optimum lordosis in PLIF reconstruction

Abstract: Purpose To examine monosegmental lordosis after posterior lumbar interbody fusion (PLIF) surgery and relate lordosis to cage size, shape, and placement. Methods Eighty-three consecutive patients underwent single-level PLIF with paired identical lordotic cages involving a wide decompression and bilateral facetectomies. Cage parameters relating to size (height, lordosis, and length) and placement (expressed as a ratio relative to the length of the inferior vertebral endplate) were recorded. Centre point ratio (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 36 publications
(49 reference statements)
5
39
0
3
Order By: Relevance
“…Our analysis also found that an anteriorly positioned cage was associated with a larger gain in SL, findings corroborated by previous investigations. 12,34 Landham et al quantified bilateral PLIF cage position using a "centre point ratio" (CPR), which represented the ratio of the distance between the posterior vertebral wall and the center of the cage to the length of the inferior endplate. 12 The investigators reported a strong correlation between the CPR and lordosis gain (r = 0.537, p < 0.001), but no association with the cage lordotic angle (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis also found that an anteriorly positioned cage was associated with a larger gain in SL, findings corroborated by previous investigations. 12,34 Landham et al quantified bilateral PLIF cage position using a "centre point ratio" (CPR), which represented the ratio of the distance between the posterior vertebral wall and the center of the cage to the length of the inferior endplate. 12 The investigators reported a strong correlation between the CPR and lordosis gain (r = 0.537, p < 0.001), but no association with the cage lordotic angle (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…7,11 The combined impact of the surgical approach, cage position, and built-in cage lordotic angle on the amount of postoperative SL achieved remains unclear. 12,13 The purpose of this study was to determine if the built-in lordotic angle of an interbody cage impacted the actual change in SL achieved with MIS lumbar interbody fusion (LIF) techniques. To our knowledge, our investigation is the largest series of MIS procedures examining the impact of cage lordotic angle on postoperative SL.…”
mentioning
confidence: 99%
“…In addition, the positioning of the cage seems to play an important role in the restoration of segmental lordosis. Anterior positioning of the cages in PLIF and TLIF techniques with short cages results in greater post-operative segmental lordosis [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…nachweisen, dass eine Cage-Implantation die Steifigkeit des Konstrukts signifikant erhöht [ 7 ]. Weiter entlastet der Cage die eingebrachten Schrauben, was einer Schraubenlockerung entgegenwirkt und die LL verbessern kann [ 2 , 5 , 6 ].…”
Section: Diskussionunclassified